What is “Folk” about Synagogue Art? - Rodov, Ilia (Images, 2016)
This publication is a tribute to the memory of the outstanding folklorist and ethnographer Dov Noy, who passed away in 2013. In the scholarly discourse that classifies folklore by modes and media of transmission, synagogue art—as distinct from folk narrative and behavioral lore—is commonly categorized as “visual folklore.” This paper examines the approach of classifying murals and sculptural decoration in east and central European synagogues from the late seventeenth century until the Holocaust as “folk creations.” It suggests a revision of pre-established definitions in the field, in general, and in the analysis of representative folk narratives relating to synagogues, in particular. The position of academic research into traditional Jewish visual culture, at the seam of art history and folkloristics, challenges predefined divisions of this integral cultural phenomenon into the conventional categories of separate disciplines. In the discourse classifying folklore according to the ways and media of its transmission, synagogue art—in distinction to folk narratives and behavioral lore—commonly falls into the category of “visual folklore,” defined as the visual domain of folk art and material culture. Jewish “folk art” is often attributed generally to “folk artists” and “craftsmen,” without a clear distinction between the two groups. This paper holistically examines the approaches to the murals and sculptural decoration in east and central European synagogues from the late seventeenth century until the Holocaust as visual folklore, craftsmanship, and artistic work, and outlines the part of oral lore in the programming and interpretation of synagogue art. Finally, it proposes to re-approach folk synagogue art as a medium that creates a visual environment for liturgical activity and predicates its viewers’ responses to the challenges, trials, and tribulations of daily life.